2023
DOI: 10.1101/2023.01.13.523858
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Drivers of asymmetrical insect invasions between three world regions

Abstract: The geographical exchange of non-native insects can be highly asymmetrical, with some world regions 'exporting' or 'importing' more species than others. Several hypotheses have been proposed to explain such asymmetries, including differences in propagule pressure, environmental features in recipient regions, or biological traits of invaders. We tested aspects of these hypotheses in the context of the exchange of non-native insects between North America, Europe, and Australasia. Europe was the dominant exporter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Yet flows of established species were on average greatest for flows originating from the Western Palearctic, Neotropical and Australasian and Oceanian regions. Similarly, Isitt et al (2023) found that Europe (i.e. the Western Palearctic) was the dominant source of established non‐native insects between North America, Europe and Australasia.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Yet flows of established species were on average greatest for flows originating from the Western Palearctic, Neotropical and Australasian and Oceanian regions. Similarly, Isitt et al (2023) found that Europe (i.e. the Western Palearctic) was the dominant source of established non‐native insects between North America, Europe and Australasia.…”
Section: Discussionmentioning
confidence: 88%
“…As well as increasing opportunities for introduction, greater trade intensity could improve the chances of species establishing through repeated introductions (Lockwood et al, 2005). Isitt et al (2023) further found no evidence for the hypothesis that a larger pool of native species leads to proportionally more species being exported. However, the history of European colonization in North America, and Australia and New Zealand may have obscured the impact of native species pool size.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…2017; Corley et al 2020; Vilardo et al 2022).An interesting nding of our study is that, although the native pool of pine bark beetles from North America is similar to the one of Eurasia(Wood and Bright 1992), the six pine bark beetle species established in South America are native to Europe and/ or Asia. This patterns of "invasion asymmetry", where the Palearctic region is over-represented and the Nearctic region under-represented as donors of non-native established species, has been commonly observed in forest insects(Mattson et al 2007;Lantschner et al 2020;Isitt et al 2023). There is no clear explanation for this pattern in our case, since the Nearctic and Palearctic regions have been historically strongly connected with the Neotropical region via trade(Lantschner et al 2020), both regions have considerable areas with similar climatic conditions differences in the evolutionary pressures between regions(Mattson et al 2007), or because of the small size of our sample.…”
mentioning
confidence: 90%